FLEXIBLE AND SECURE ACCESS TO COMPUTING CLUSTERS - Meizner, Jan; Malawski, Maciej; Bubak, Marian (Computer Science, 2013)
The investigation presented in this paper was prompted by the need to provide a manageablesolution for secure access to computing clusters with a federated authentication framework.This requirement is especially important for scientists who need direct access to computingnodes in order to run their applications (e.g. chemical or medical simulations) with proprietary,open-source or custom-developed software packages. Our existing software, whichenables non-Web clients to use Shibboleth-secured services, has been extended to providedirect SSH access to cluster nodes using the Linux Pluggable Authentication Modules mechanism.This allows Shibboleth users to run the required software on clusters. Validationand performance comparison with existing SSH authentication mechanisms confirm that thepresented tools satisfy the stated requirements.